MCDA twins with discordant malformations: submicroscopic chromosomal anomalies detected by chromosomal microarray analysis and clinical outcomes. (14th July 2016) - Peng, Ruan; Zhou, Yi; Xie, Hong‐Ning; Zheng, Ju; Xie, Ying‐Jun; Yang, Jian‐Bo
Abstract: Objective: To evaluate whether discrepant copy number variations (CNVs) contribute to the risk for discordant congenital anomalies in monochorionic diamniotic (MCDA) twins. Methods: We conducted a parallel testing using both G‐banding for standard karyotyping and chromosomal microarray analysis (CMA) with Affymetrix CytoScan HD array in MCDA twins with discordant malformations. Results: During the study period, 193 MCDA twins with discordant malformations were detected and followed up. Multiple anomalies and cardiac defects were detected most frequently among the fetuses with malformations. Among all the 119 MCDA twins that were successfully performed fetal karyotyping, discordance of chromosomal aberrations were identified in nine cases, including one with discordant trisomy 18, seven with discordant monosomy X, one twin with 47, XXY and the co‐twin with 45, X [7]/46, XY[43]. CMA revealed pathological CNVs in four out of the 110 fetuses with normal karyotype and the detection rate of uncertain clinical significance was 3.6% (4/110). Discordance of CNVs was detected in 5.5% (3/55) among the 55 MCDA twins with normal karyotype. Monozygosity was confirmed in all the 61 MCDA twins that were performed CMA. Conclusions: Large whole chromosome abnormalities are more common between discordant twins rather than smaller CNVs in this study. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known about this Topic? Genetic mechanisms have been reported that may result in phenotypic differences between monozygous twins. Previous reported studies focusing on discordance CNVs in MZ twins were performed in postnatal patients. What does this Study Add? This study reported that discordance of karyotype was identified in 7.6% (9/119) and discordance of CNVs in 5.5% (3/55) in MCDA twins with discordant malformations and large whole chromosome abnormalities are more common rather than smaller CNVs in our study.